Law Enforcement Against Spatial Planning Violations in Housing Development: Challenges, Governance, and Regulatory Compliance - Arie Sigit; Nur Handayati; Fitri Ayuningtyas; Vieta Imelda Cornelis (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the implementation of law enforcement against spatial planning violations in housing development, identify the factors affecting its effectiveness, and examine strategies to strengthen legal compliance in sustainable housing development.Research Methodology: This study employed a qualitative method using an empirical juridical approach. Data were collected through in-depth interviews, document analysis, observation, and literature review. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing, with source and method triangulation to ensure credibility. Results: The findings indicate that law enforcement against spatial planning violations has not been fully effective due to weak institutional coordination, limited supervision, inadequate integration of spatial data, and inconsistent implementation of legal sanctions. Administrative sanctions remain the dominant enforcement mechanism, while preventive monitoring and public participation require significant improvement.Conclusions: Effective law enforcement requires integrated governance, stronger institutional capacity, consistent supervision, updated spatial planning instruments, and active collaboration among government agencies, law enforcement institutions, and developers.Limitations: This study is limited to a qualitative analysis of housing development cases and does not include comparative regional analysis or quantitative measurement of law enforcement effectiveness.Contributions: This study contributes to the development of spatial planning law by providing practical recommendations for strengthening law enforcement, improving spatial governance, and supporting sustainable housing development policies in Indonesia.